PUBLIC SPENDING AS A NEW DETERMINATE OF SUSTAINABLE DEVELOPMENT GOAL AND GREEN ECONOMIC RECOVERY: POLICY PERSPECTIVE ANALYSIS IN THE POST-COVID ERA - Liu, Zhen; Yin, Tong; Surya Putra, Ahmad Romadhoni; Sadiq, Muhammad (2022)
Green economy talks about combing final mechanisms that have ecological and macroeconomic system gains. Likewise, this research piece examined the effects of increased spending on fiscal policies and tightening fiscal policies concerning greening the economic activity as the globe reclaims itself from the COVID-19 in China. Analysis was done applying the China longitudinal data for the period 2008-2018. We utilized the ordinary least square as well as the quantile regression equation to meticulously approximate the influences of increased fiscal spending policies in addition to tightening fiscal policies has on greening the economic system acts as the countries reclaim themselves from the pandemic via a formulated green performance indicator of China nations. The findings indicate a rather exciting pattern by saying a percentage growth in fiscal policy led to nearly 6.5 growth, that is, less than 0.5 growth in the minimum carbon dioxide polluting vaporous from energy suppliers, such as natural gas, and a 0.2 less than 0.01 cuts in the midway carbon dioxide polluting liquefied energy suppliers, that is, hydrocarbon byproducts and a nonsignificant expansion of 0.2, more significant than 0.5 in the entire case scenario coming from polluting dense energy suppliers, that is, from coal byproduct sources. At the same time, a 1 expansion in fiscal policy reduces cumulative carbon dioxide pollution to 0.2, less than 0.05. On this score, the presence of the environmental hypothesis was authenticated in all scenarios analyzed. Furthermore, the causality test indicated a dual movement causative correlation between fiscal policy and carbon dioxide pollution and one-way movement concerning the fiscal policy to energy use. The findings demonstrated that China witnessed a rising switch to green advancement in China; their Green Economic Efficiency increased steadily. © 2022 World Scientific Publishing Company.